FAMILY SOCIALISATION FUNCTION IN OUT-OF-SCHOOL CHILDREN - Nikita Khoerunnisa; Nurhadi Nurhadi; Dwi Astutik (Hudan Lin Naas: Jurnal Ilmu Sosial dan Humaniora, 2023)
The Wonosobo District Government has endeavored to tackle the problem of out-of-school children through the "Mayo Sekolah" program. However, not all children, including those in Jaraksari Urban Village, show interest in resuming their education. Various studies have shown that family factors contribute to children's decision not to attend school. This research seeks to explore the function of family socialization in out-of-school children by exploring their life experiences from the time they decide not to go to school to their plans. This qualitative research with a grounded theory approach was conducted using interviews, observation, and documentation. In-depth interviews were conducted with five primary informants of out-of-school children and five supporting informants in the form of informants' families. Observation was conducted by observing the activities of out-of-school children. Documentation was conducted by analyzing documents from Jaraksari Urban Village, the Education Office, and various relevant reading sources. The study results were analyzed using Spradley's data analysis technique, which consists of domain analysis, taxonomy analysis, component analysis, and theme analysis. Meanwhile, data validity was tested using source triangulation. The results showed that the conjugal family system influences the function of family socialization. Three variations of conjugal families become the place of growth of out-of-school children in Jaraksari Urban Village, namely families who live separately from their extended families, families who experience problems within the scope of the nuclear family, and families who live with extended families but remain independent in carrying out their respective functions.